Profile of Apoptotic Marker Genes and Histopathology of the Placenta in Pregnancies with Pre-Eclampsia - Herlambang, Herlambang; Enis, Rina Nofri; Tarawifa, Susan; Harahap, Huntari; Puspasari, Anggelia; Maharani, Citra; Kusdiyah, Erny (Althea Medical Journal, 2023)
Background: Pre-eclampsia (PE) is a hypertensive disorder in pregnancy and a significant cause of maternal and perinatal mortality and morbidity. Failure of spiral artery remodeling due to abnormal apoptosis, triggers disturbances in the mother and the baby’s growth. This study aimed to identify the profile of apoptotic marker genes and histopathological features of the placenta in pregnancies with pre-eclampsia.Methods: This study had used case-control method. Samples were taken from normal pregnancies (n=25) and pregnant women with pre-eclampsia (n=25) using a purposive sampling method from several hospitals in Jambi. qRT-PCR was used to examine apoptotic gene expression from placental tissue and hematoxyline eosin staining to view the placenta’s microscopic appearance. The targeted genes were BCL2-associated X (BAX) and B-cell lymphoma 2 (BCL-2). Histopathological changes of the placenta observed were syncytial node, cytotrophoblast, villous edema, hypervascularization, fibrosis stroma, atherosis, infarction, and thrombosis.Results: Relative BAX genes expression were increased once in placenta pre-eclampsia compared to controls, but not statistically significant (p-value>0.05). There was no difference between the decline of BCL-2 gene expression in pre-eclampsia placenta compared to the control (p-value >0.05). Histopathological changes in the placenta were syncytial node and cytotrophoblast (25 of 25), villous edema (19 of 25), hypervascularization (24 of 25), fibrosis stroma (22 of 25), atherosis (12 of 25), infarction (17 of 25), and thrombosis (24 of 25).Conclusion: The expression of BAX genes in pre-eclampsia tends to increase compared to normal pregnancy, and the expression of BCL-2 decreases.  The histopathological features of pre-eclampsia pregnancy placenta are mostly syncytial nodes, cytotrophoblasts, stromal fibrosis, and thrombosis.